Survey of image style transfer based on neural network - Liu Jianfeng; Zhong Guoyun (Dianzi Jishu Yingyong, 2022)
In order to promote the research of image style transfer technology based on neural network, the main methods and representative work of image style transfer based on neural network are summarized and discussed in this paper. This paper reviews the traditional style transfer algorithms, introduces the basic principles and methods of the main image style transfer based on neural network in detail, analyzes the application prospect of the related field of image style transfer based on neural network, and finally summarizes the existing problems and future research direction of the image style transfer based on neural network.